The Concept of Child Custody (Hadhanah) After Divorce in the Perspective of Islamic Law - Umar Multazam (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2024)
This research discusses post-divorce child custody (hadhanah) disputes in Indonesia which are resolved in religious courts based on substantive and formal law. The Qur’an and hadith do not explicitly mention hadhanah, but the verses about breastfeeding and fathers' obligations are close to the concept of child custody. The obligations of parents after marriage are to care for, protect, educate, and care for children until adulthood, with the determination of custody by a judge after a divorce it can fall to the mother or father. This research aims to understand the concept of child custody after divorce according to the Qur’an and hadith, juridical review, and the legal consequences. The method used is qualitative with the type of Library Research, collecting data through documentation and triangulation analysis. The research results show that assigning custody to the mother or father does not conflict with regulations as long as the child's best interests are met, and both mother and father have the right to care for the child, although the mother has more rights. In conclusion, determining child custody after divorce must guarantee the child's best interests following applicable regulations.